ADDITIONAL OPPORTUNITIES FOR THE DEVELOPMENT OF TOURISM IN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In this article, tourism, tourism infrastructures, modern tourism sector, additional investment, rapid development of tourism potential, tourist flow, international airports, additional opportunities for tourism development in Uzbekistan, issues of increasing tourism potential, tourist visits, tourist arrivals gate airport, tourism programs, the role of cultural heritage objects in tourism, its development and organization, attracting tourists, unique achievements, lifestyle , even turf traditions, video selector on increasing the potential of tourism, statistical analysis of tourism in our country, problems related to plane and train tickets in the implementation of tourist visits, achievements and shortcomings indicated by the head of our country in the field of tourism, means of placement, information about tourism programs, keeping tourists in our country for a longer period of time, and the issues of the World Tourism Organization and "Uzbekistan business card".